The Social Communication Competence as a Soft Skill of the School Leadership in Archipelago Region - Ismail, Khodijah Ismail; Sutarman; Tumin; Yudhakusuma, Dudi; Mayasari, Linda Ika (International Journal of Psychosocial Rehabilitation, 2020)
Education is an important part of development in coastal areas and border islands because it has specific demographic and geographic characteristics. Therefore a leadership style that is able to understand this specific situation is needed. This study aims to examine the application of principals’ social communication skills in situational leadership styles to improve teacher / student interaction and ultimately improve teacher performance and the learning process of madrasah schools in the coastal areas of the border island. This research was conducted at MAN Tanjungpinang, Riau Islands. Data collection using questionnaires and interviews with 28 teachers, with a quantitative approach. The results showed that there was a positive relationship between the principal’s situational leadership style and teacher performance (significant value (P-value) of 0.049 <0.05) with a contribution rate of 14.06%. Principal’s leadership style and teacher performance are in the medium category with scores of 92.86% and 89.29%, respectively. The principal’s situational leadership style is largely determined by the ability of social communication as a soft skill he has. The soft skill of the school principal’s social communication results in better teacher performance and influences student academic and non-academic achievement (good and communicative personality). Contextually and situationally, in order to produce good teacher performance and student achievement for schools in the coastal areas of the border island, it is necessary to have the leadership of the principal and teachers who have good social communication skills.